Steven-Johnson Syndrome (SJS) in a Multiple Myeloma patient treated with lenalidomide and low dose dexamethasone regimen: a rare Case Report - Lohit kumar Kalita; Chayanika Kalita; Pabitra Kamar Gogoi; Umesh Ch. Sarma (International Journal of Medical Research and Review, 2015)
Lenalidomide is an immunomodulatory drug (IMiD), a derivative of thalidomide used in the treatment of multiple myeloma. Stevens-Johnson syndrome (SJS) is a rare but life-threatening cutaneous adverse reaction, at a rate of 1.1 to 7.1 cases per million person-years, mortality rate between 1% to 3% and 10% to 70% when it is associated with TIN. Very few cases of Lenalidomide induced SJS has been reported. We describe a case of Stevens-Johnson syndrome induced by induction therapy lenalidomide-low dose Dexamethasone regimen in a 56 year-old male who underwent induction therapy for multiple myeloma.